EROSIVE PUSTULAR DERMATOSIS OF THE SCALP – A CASE REPORT - Cakić, Jelena; Tanasilović, Srđan; Vuković, Jelena; Živanović, Dubravka (Medical Research, 2024)
Introduction: Erosive pustular dermatosis of the scalp (EPDS) is a rare, inflammatory, dermatosis of unknown etiology, which mainly affects the scalp. The condition is characterized by sterile pustules, that often become secondarily colonized, erosions and crusts which lead to scarring alopecia. EPDS occurs in elderly, more frequent in women.Patient review: A 55-year-old Caucasian female presented with a large atrophic erythematous plaque on the scalp, coated with pustules on the sides and covered with thick crusts and erosions. The patient reported a history of painless, moderate itching, enlarging lesions during three months prior admission to our department. She had no history of trauma, sun exposure or some medical or cosmetic treatment (topical and systemic). Serological and immunologic tests were negative. Fungal stains were negative. Bacterial cultures grew Staphylococcus aureus.  A scalp biopsy revealed polymorphous inflammatory infiltrate in the dermis of neutrophils, lymphocytes and plasma cells. Direct immunofluorescence test was negative. Treatment with oral antibiotic (rimfapicine) and potent topical corticosteroids led to marked and quick improvement but with remaining scarring alopecia.  Conclusion EPDS is a diagnosis of exclusion, based on clinical presentation, disease course and histopathological findings. It is necessary to exclude other diseases - autoimmune bullous disorders, malignancies, neutrophilic dermatoses, bacterial and fungal infections. Prompt diagnosis and treatment will reduce scarring.
Keywords: erosive pustular dermatosis; trauma; diagnosis; treatment